Polishing pad and method for manufacturing the same

The polishing pad with controlled pore distribution and hollow microspheres addresses the issue of debris accumulation, enhancing polishing rate and defect performance for optical and semiconductor surfaces.

JP2025013614APending Publication Date: 2025-01-24FUJIBO HLDG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024195811
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing polishing pads have insufficient polishing rates and defect performance due to large pores that accumulate polishing debris, leading to inadequate surface finishing of optical materials, semiconductor wafers, and hard disk substrates.

Method used

A polishing pad with a polishing layer containing hollow microspheres, where the cross-section has an average pore diameter of 10 to 14 μm, with less than 5% of openings larger than 25 μm and 20% of the total area occupied by pores larger than 25 μm, ensuring uniform distribution and reduced debris retention.

Benefits of technology

The polishing pad achieves a good polishing rate with excellent defect performance by minimizing debris accumulation, resulting in improved surface quality for optical materials and semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013614000001_ABST
    Figure 2025013614000001_ABST
Patent Text Reader

Abstract

To provide a polishing pad capable of simultaneously achieving a high polishing rate and defect performance.SOLUTION: This polishing pad comprises a polishing layer having a polishing surface for polishing an article to be polished. The polishing layer includes a hollow microsphere having a hollow body formed within the polishing layer. The cross-section of the polishing layer has an average open hole diameter of 10-14 μm. In an open hole diameter histogram of the cross-section of the polishing layer represented with a range of 1 μm as one grade, the sum total of open holes of 25 μm or more is 5% or lower of the number of all open holes on the cross-section, and the sum total of the open hole area of each grade of 25 μm or more is 20% or lower of the total open hole area of the cross-section.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing pad. In particular, the present invention relates to a polishing pad that can be suitably used for polishing optical materials, semiconductor wafers, semiconductor devices, hard disk substrates, and the like. [Background technology]

[0002] Chemical mechanical polishing (CMP) is commonly used as a polishing method for planarizing the surfaces of optical materials, semiconductor wafers, semiconductor devices, and hard disk substrates.

[0003] The CMP method will be described with reference to FIG. 1. As shown in FIG. 1, a polishing apparatus 1 for carrying out the CMP method is provided with a polishing pad 3, which contacts an object 8 to be polished held on a holding platen 16 and includes a polishing layer 4, which is a layer for polishing, and a cushion layer 6 for supporting the polishing layer 4. The polishing pad 3 is rotated while the object 8 to be polished is pressed against it, and polishes the object 8 to be polished. At that time, a slurry 9 is supplied between the polishing pad 3 and the object 8 to be polished. The slurry 9 is a mixture (dispersion liquid) of water, various chemical components, and hard fine abrasive grains, and the chemical components and abrasive grains in the slurry are flowed and move relative to the object 8 to increase the polishing effect. The slurry 9 is supplied to the polishing surface through grooves or holes and discharged.

[0004] By the way, the polishing pad used for polishing semiconductor devices usually has a polishing layer made of synthetic resin such as polyurethane, and voids are formed inside this polishing layer. Since this void is open on the surface of the polishing layer, the abrasive grains contained in the polishing slurry are held during polishing, and the polishing of the object to be polished progresses. As a method for forming such voids, a method of mixing hollow microspheres in resin is conventionally known. In recent years, in order to realize more precise polishing, the reduction in diameter and uniformity of hollow microspheres have been studied.

[0005] Patent Document 1 discloses a polishing pad that contains unexpanded hollow microspheres having an average particle size of 20 μm or less and has a high density and excellent polishing rate.

[0006] Furthermore, Patent Document 2 discloses a polishing pad that has a wide pore distribution and enables adjustment of polishing performance by using a solid-phase foaming agent such as hollow microspheres and a gas-phase foaming agent such as an inert gas. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-069497 A [Patent Document 2] JP 2019-069507 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the polishing pads described in Patent Documents 1 and 2 have a high proportion of pores larger than 25 μm in the distribution of pore diameters measured on the cross section of the polishing layer, and polishing debris and the like can become trapped in these pores, resulting in insufficient defect performance.

[0009] The present invention has been made in consideration of the above problems, and has an object to provide a polishing pad that can achieve both a good removal rate and good defect performance. [Means for solving the problem]

[0010] As a result of extensive research, the present inventors have discovered a polishing pad that uses predetermined hollow microspheres and thereby achieves both a good removal rate and good defect reduction performance. [1] A polishing pad having a polishing layer having a polishing surface for polishing an object to be polished, the polishing layer includes hollow microspheres that form hollow bodies within the polishing layer; The cross section of the polishing layer has an average pore size of 10 to 14 μm, In a histogram of opening diameters of a cross section of the polishing layer, the range of 1 μm is expressed as one class, The sum of the number of pores having a size of 25 μm or more is 5% or less of the total number of pores in the cross section, A polishing pad, wherein the sum of the open area of ​​each class of 25 μm or more is 20% or less of the total open area of ​​the cross section. [2] The polishing pad described in [1], wherein the sum of the number of pores in each class of 30 μm or more is 3% or less of the total number of pores in the polishing surface, and the sum of the area of ​​pores in each class of 30 μm or more is 10% or less of the total area of ​​pores in the polishing surface. [3] The polishing pad according to [1] or [2], wherein the hollow microspheres are derived from unexpanded hollow microspheres having a median diameter (D50) of 6 μm or less. [4] A method for manufacturing a polishing pad having a polishing layer having a polishing surface for polishing an object to be polished, comprising the steps of: the polishing layer includes hollow microspheres that form hollow bodies within the polishing layer; The cross section of the polishing layer has an average pore size of 10 to 14 μm, In a histogram of opening diameters of a cross section of the polishing layer, the range of 1 μm is expressed as one class, The sum of the number of pores having a size of 25 μm or more is 5% or less of the total number of pores in the cross section, The sum of the open area of ​​each class of 25 μm or more is 20% or less of the total open area of ​​the cross section, The polishing layer is formed by mixing and reacting a urethane bond-containing polyisocyanate compound, a curing agent, and unexpanded hollow microspheres having a median diameter (D50) of 6 μm or less. [5] The method of [4], wherein the reaction is carried out under temperature control so as not to exceed 140°C. [6] A polishing method for polishing an object to be polished using a polishing pad and abrasive grains, comprising: The polishing pad includes a polishing layer having a polishing surface for polishing an object to be polished, the polishing layer includes hollow microspheres that form hollow bodies within the polishing layer; The cross section of the polishing layer has an average pore size of 10 to 14 μm, In a histogram of opening diameters of a cross section of the polishing layer, the range of 1 μm is expressed as one class, The sum of the number of pores having a size of 25 μm or more is 5% or less of the total number of pores in the cross section, The sum of the open area of ​​each class of 25 μm or more is 20% or less of the total open area of ​​the cross section, The abrasive grains have a diameter of 0.01 to 0.2 μm, A polishing method comprising the steps of: bringing the object to be polished into contact with the polishing surface of the polishing pad in the presence of the abrasive grains; and rotating either or both of the polishing pad and the object to be polished, thereby performing polishing. Effect of the Invention

[0011] A polishing pad having a polishing layer containing certain hollow microspheres provides good removal rates and has excellent defect performance. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a perspective view of a polishing apparatus 1. As shown in FIG. [Diagram 2] FIG. 2 is a cross-sectional view of the polishing pad. [Diagram 3] FIG. 3 shows enlarged photographs of the polishing layers of the polishing pads of Example 1 and Comparative Example 1, and their pore size histograms. [Figure 4] FIG. 4 shows enlarged photographs of the polishing layers of the polishing pads of Example 2 and Comparative Example 2, and their pore size histograms. [Figure 5a] FIG. 5a shows the change in polishing rate when a metallic copper film is polished using the polishing pads of Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 5b] FIG. 5b shows the number of defects when a metallic copper film was polished using Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 6a]FIG. 6a shows the change in polishing rate when a silicon oxide film is polished using the polishing pads of Examples 1 and 2 and Comparative Examples 1 and 2. [Figure 6b] FIG. 6b shows the number of defects when a silicon oxide film is polished using Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, a mode for carrying out the invention will be described, however, the present invention is not limited to the mode for carrying out the invention.

[0014] <<Polishing pad>> The polishing pad of the present invention provides a good polishing rate and has excellent defect performance. In this specification, "particle" means fine particles remaining in the polishing slurry or the like that are attached to the surface of the polished object, "pad debris" means debris of the polishing layer that is generated by the surface of the polishing layer of the polishing pad being worn during the polishing process that is attached to the surface of the polished object, and "scratch" means scratches on the surface of the polished object. In this specification, "defect" is a general term including the above-mentioned particles, pad debris, scratches, etc.

[0015] The structure of the polishing pad 3 will be described with reference to Fig. 2(a). As shown in Fig. 2(a), the polishing pad 3 includes a polishing layer 4 and a cushion layer 6. The shape of the polishing pad 3 is preferably disc-shaped, but is not particularly limited thereto, and the size (diameter) can also be appropriately determined depending on the size of the polishing apparatus 1 equipped with the polishing pad 3, and can be, for example, about 10 cm to 2 m in diameter. In the polishing pad 3 of the present invention, the polishing layer 4 is preferably bonded to the cushion layer 6 via an adhesive layer 7, as shown in FIG. 2(a). The polishing pad 3 is attached to a polishing platen 10 of the polishing device 1 by double-sided tape or the like arranged on the cushion layer 6. The polishing pad 3 is rotated by the polishing device 1 while pressing against an object 8 to be polished, and polishes the object 8 (see FIG. 1).

[0016] <Polishing layer> (composition) The polishing pad 3 includes a polishing layer 4 that is a layer for polishing an object to be polished 8. The material constituting the polishing layer 4 can be suitably selected from polyurethane resin, polyurea resin, and polyurethane-polyurea resin, and more preferably polyurethane resin. The size (diameter) of the polishing layer 4 is the same as that of the polishing pad 3 and can be about 10 cm to 2 mm in diameter, and the thickness of the polishing layer 4 can usually be about 1 to 5 mm. The polishing layer 4 is rotated together with the polishing platen 10 of the polishing device 1, and while a slurry 9 is poured onto it, the chemical components and abrasive grains contained in the slurry 9 are moved relative to the object 8 to be polished, thereby polishing the object 8 to be polished. Hollow microspheres 4A are dispersed in the polishing layer 4. When the polishing layer 4 is worn down, the hollow microspheres 4A are exposed on the polishing surface, generating minute voids on the polishing surface. These minute voids hold the slurry, allowing polishing of the workpiece 8 to proceed more rapidly.

[0017] The polishing layer 4 is formed by casting a mixture of a urethane bond-containing polyisocyanate compound (prepolymer) containing hollow microspheres 4A (described later) and a curing agent (chain extender), and slicing the cured foam. In other words, the polishing layer 4 is dry molded.

[0018] (Hollow microspheres) The hollow microspheres 4A contained in the polishing layer 4 of the polishing pad of the present invention can be confirmed as hollow bodies on the polishing surface of the polishing layer 4 or on the cross section of the polishing layer 4. The hollow microspheres 4A contained in the polishing layer 4 usually have a diameter (or opening diameter) of 2 to 200 μm. The shape of the hollow microspheres 4A can be spherical, elliptical, or similar shapes. In the polishing layer 4 of the present invention, the average pore size of the pores on the cross section or polishing surface formed by the hollow microspheres is 10 to 14 μm. When the average pore size is in this range, the slurry (or the abrasive grains contained in the slurry) can be properly held, and a good polishing rate can be achieved. Setting the average pore size to less than 10 μm is not practical because it requires the use of special hollow microspheres, and there are problems such as difficulty in manufacturing and handling, and costs. Also, if it is more than 14 μm, it may cause defects.

[0019] Furthermore, the pores in the cross section or polishing surface of the polishing layer 4 of the polishing pad of the present invention have a specific pore size distribution. To represent the pore size distribution, a pore size histogram is used herein, in which one class is shown for each 1 μm range. In this specification, a class is defined as a range of 1 μm intervals of the measured pore size (for example, 20.0 μm or more, less than 21.0 μm, etc.).

[0020] In the present invention, the total number of apertures of 25 μm or more is 5% or less of the total number of apertures in the cross section of the polishing layer. If the total number of apertures of 25 μm or more is 5% or less of the total number of apertures in the cross section, the apertures of 25 μm or more are few and there is no bias in the number of apertures, which is considered to affect good defect performance. In addition, preferably, the total number of apertures of each class of 25 μm or more is 5% or less of the total number of apertures in the cross section of the polishing layer. In other words, the total number of apertures of 25 μm or more and less than 26 μm is 5% or less of the total number of apertures in the cross section of the polishing layer, and the total number of apertures of 26 μm or more and less than 27 μm is 5% or less of the total number of apertures in the cross section of the polishing layer, and the same applies to each class of 27 μm or more. In addition, the total number of apertures of each class of 30 μm or more is preferably 3% or less of the total number of apertures in the cross section.

[0021] In addition, in the present invention, the sum of the aperture areas of each class of 25 μm or more is 20% or less of the total aperture area of ​​the cross section. If the sum of the aperture areas of each class of 25 μm or more is 20% or less of the total aperture area of ​​the cross section, the possibility of retaining polishing debris and the like in the apertures is low, which is also considered to affect good defect performance. In addition, for apertures of 30 μm or more that are more likely to retain polishing debris and the like, it is preferable that the sum of the aperture areas of each class of 30 μm or more is 10% or less of the total aperture area of ​​the cross section.

[0022] The hollow microspheres 4A may be commercially available balloons, and may be of the expanded or unexpanded type. The unexpanded type is a thermally expandable microsphere, which can be expanded by applying heat.

[0023] In the present invention, it is preferable to mix unexpanded hollow microspheres together with the urethane bond-containing polyisocyanate compound (prepolymer) and the curing agent that form the polishing layer 4. By using unexpanded hollow microspheres, the diameter (opening diameter) of the hollow microspheres 4A can be made small. In addition, when using unexpanded hollow microspheres, the reaction between the prepolymer and the curing agent is carried out after the unexpanded hollow microspheres are incorporated, so that the diameter tends to be larger than that in the unexpanded state due to the reaction heat, and the diameter may be larger than expected depending on the temperature. In order to suppress this, it is preferable to control the reaction temperature so that it does not become too high and does not exceed a predetermined temperature. The reaction temperature depends on the gas components contained in the unexpanded hollow microspheres, but is preferably 140°C or less, and more preferably 100°C or less.

[0024] (Groove machining) The surface of the polishing layer 4 of the present invention facing the polished object 8 may be provided with grooves. The grooves are not particularly limited, and may be either slurry discharge grooves communicating with the periphery of the polishing layer 4 or slurry holding grooves not communicating with the periphery of the polishing layer 4, or may have both slurry discharge grooves and slurry holding grooves. Examples of the slurry discharge grooves include lattice grooves and radial grooves, and examples of the slurry holding grooves include concentric grooves and perforations (through holes), and these may also be combined.

[0025] <Cushion layer> (composition) The polishing pad 3 of the present invention has a cushion layer 6. It is desirable for the cushion layer 6 to make the contact of the polishing layer 4 with the polished object 8 more uniform. The material of the cushion layer 6 may be any of impregnated nonwoven fabric impregnated with resin, flexible materials such as synthetic resins and rubber, and foams having a cellular structure. Examples of the material include resins such as polyurethane, polyethylene, polybutadiene, and silicone, and rubbers such as natural rubber, nitrile rubber, and polyurethane rubber. From the viewpoint of adjusting the density and compressive elastic modulus, an impregnated nonwoven fabric is preferable, and polyurethane is preferably used as the material impregnated into the nonwoven fabric.

[0026] The cushion layer 6 is preferably made of a polyurethane resin having sponge-like fine bubbles.

[0027] The compressive elastic modulus, density, and bubbles of the cushion layer 6 in the polishing pad 3 of the present invention are not particularly limited, and a cushion layer 6 having known characteristic values ​​can be used.

[0028] <Adhesive layer> The adhesive layer 7 is a layer for adhering the cushion layer 6 and the polishing layer 4, and is usually made of a double-sided tape or adhesive. The double-sided tape or adhesive may be any known double-sided tape or adhesive in the art (e.g., an adhesive sheet). The polishing layer 4 and the cushion layer 6 are bonded together by an adhesive layer 7. The adhesive layer 7 can be made of at least one adhesive selected from, for example, acrylic, epoxy, and urethane adhesives. For example, an acrylic adhesive is used, and the thickness can be set to 0.1 mm.

[0029] <<Polishing pad manufacturing method>> A method for producing the polishing pad 3 of the present invention will now be described.

[0030] <Abrasive layer material> The material of the polishing layer is not particularly limited, but the main component is preferably a polyurethane resin, a polyurea resin, or a polyurethane polyurea resin, and more preferably a polyurethane resin. A specific main component material may be, for example, a material obtained by reacting a urethane bond-containing polyisocyanate compound (prepolymer) with a curing agent.

[0031] Hereinafter, a method for producing the material of the polishing layer 4 will be described using an example in which a urethane bond-containing isocyanate compound and a curing agent are used.

[0032] Examples of a method for producing the polishing layer 4 using a urethane bond-containing polyisocyanate compound and a curing agent include a production method including: a material preparation step of preparing at least a urethane bond-containing polyisocyanate compound, an additive, and a curing agent; a mixing step of mixing at least a urethane bond-containing polyisocyanate compound, an additive, and a curing agent to obtain a mixed liquid for molding a molded body; and a curing step of molding the mixed liquid for molding a molded body into a polishing layer.

[0033] The material preparation process, the mixing process, and the molding process will be explained below.

[0034] <Material preparation process> To manufacture the polishing layer 4 of the present invention, a urethane bond-containing polyisocyanate compound and a curing agent are prepared as raw materials for a polyurethane resin molded body (cured resin). Here, the urethane bond-containing polyisocyanate is a prepolymer (urethane prepolymer) for forming a polyurethane resin molded body. When the polishing layer 4 is to be a polyurea resin molded body or a polyurethane-polyurea resin molded body, a prepolymer appropriate for the purpose is used.

[0035] Each component will be described below.

[0036] (Polyisocyanate compound containing urethane bonds) The urethane bond-containing polyisocyanate compound (urethane prepolymer) is a compound obtained by reacting the following polyisocyanate compound with a polyol compound under commonly used conditions, and contains a urethane bond and an isocyanate group in the molecule. In addition, other components may be contained in the urethane bond-containing polyisocyanate compound within the range that does not impair the effects of the present invention.

[0037] The urethane bond-containing polyisocyanate compound may be a commercially available product, or may be a product synthesized by reacting a polyisocyanate compound with a polyol compound. The reaction is not particularly limited, and addition polymerization may be performed using a method and conditions known in the production of polyurethane resins. For example, the polyisocyanate compound may be added to a polyol compound heated to 40°C while stirring in a nitrogen atmosphere, and the temperature may be raised to 80°C after 30 minutes, and the reaction may be continued at 80°C for 60 minutes.

[0038] (Polyisocyanate compounds) In this specification, the polyisocyanate compound means a compound having two or more isocyanate groups in the molecule. The polyisocyanate compound is not particularly limited as long as it has two or more isocyanate groups in the molecule. For example, diisocyanate compounds having two isocyanate groups in the molecule include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), naphthalene-1,4-diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), 4,4'-methylene-bis(cyclohexyl isocyanate) (hydrogenated MDI), 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3'-dimethyl- Examples of the polyisocyanate include diphenylmethane-4,4'-diisocyanate, xylylene-1,4-diisocyanate, 4,4'-diphenylpropane diisocyanate, trimethylene diisocyanate, hexamethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, p-phenylene diisothiocyanate, xylylene-1,4-diisothiocyanate, ethylidine diisothiocyanate, etc. These polyisocyanate compounds may be used alone or in combination of a plurality of polyisocyanate compounds.

[0039] The polyisocyanate compound preferably contains 2,4-TDI and / or 2,6-TDI.

[0040] (Polyol compounds as raw materials for prepolymers) In this specification, the polyol compound means a compound having two or more hydroxyl groups (OH) in the molecule. Examples of polyol compounds used in the synthesis of a urethane bond-containing polyisocyanate compound as a prepolymer include diol compounds, triol compounds, etc., such as ethylene glycol, diethylene glycol (DEG), butylene glycol, etc.; and polyether polyol compounds, such as poly(oxytetramethylene) glycol (or polytetramethylene ether glycol) (PTMG). Among these, PTMG is preferred. The number average molecular weight (Mn) of PTMG is preferably 500 to 2000, more preferably 600 to 1300, and even more preferably 650 to 1000. The number average molecular weight can be measured by gel permeation chromatography (GPC). When measuring the number average molecular weight of a polyol compound from a polyurethane resin, each component can be decomposed by a conventional method such as amine decomposition, and then the number average molecular weight can be estimated by GPC. The above polyol compounds may be used alone or in combination of two or more.

[0041] (Additives) As described above, additives such as an oxidizing agent can be added to the material of the polishing layer 4, if necessary.

[0042] (hardening agent) In the method for producing the polishing layer 4 of the present invention, a curing agent (also called a chain extender) is mixed with a urethane bond-containing polyisocyanate compound, etc. in a mixing step. By adding the curing agent, in the subsequent molding step, the main chain terminal of the urethane bond-containing polyisocyanate compound bonds with the curing agent to form a polymer chain, which then hardens. Examples of the curing agent include ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis[3-(isopropylamino)-4- polyamine compounds such as 2,2-bis[3-(1-methylpropylamino)-4-hydroxyphenyl]propane, 2,2-bis[3-(1-methylpentylamino)-4-hydroxyphenyl]propane, 2,2-bis(3,5-diamino-4-hydroxyphenyl)propane, 2,6-diamino-4-methylphenol, trimethylethylene bis-4-aminobenzoate, and polytetramethylene oxide-di-p-aminobenzoate; ethylene glycol, Pyrene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3- Examples of polyhydric alcohol compounds include methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, glycerin, trimethylolpropane, trimethylolethane, trimethylolmethane, poly(oxytetramethylene) glycol, polyethylene glycol, and polypropylene glycol.The polyamine compound may have a hydroxyl group, and examples of such amine compounds include 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, etc. As the polyamine compound, a diamine compound is preferable, and it is more preferable to use, for example, 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylenebis-o-chloroaniline) (hereinafter abbreviated as MOCA).

[0043] The polishing layer 4 includes hollow microspheres 4A having an outer shell and a hollow interior. As described above, the material of the hollow microspheres 4A can be a commercially available product. Alternatively, a product obtained by synthesis using a conventional method can be used. The material of the outer shell of the hollow microspheres 4A is not particularly limited, and examples thereof include polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyethylene glycol, polyhydroxyether acrylate, maleic acid copolymer, polyethylene oxide, polyurethane, poly(meth)acrylonitrile, polyvinylidene chloride, polyvinyl chloride and organic silicone resins, and copolymers of two or more types of monomers constituting these resins. In addition, examples of commercially available hollow microspheres include, but are not limited to, Expancel series (trade name manufactured by Akzo Nobel), Matsumoto Microsphere (trade name manufactured by Matsumoto Yushi Co., Ltd.), and the like.

[0044] The shape of the hollow microspheres 4A is not particularly limited, and may be, for example, spherical or nearly spherical. As described above, it is preferable to use unexpanded hollow microspheres as the raw material.

[0045] Depending on the size of the hollow microspheres before being mixed with the resin, the openings in the polishing layer 4 obtained by the reaction can be adjusted to an appropriate size. In particular, unexpanded hollow microspheres are preferable because they are smaller than expanded hollow microspheres. The unexpanded hollow microspheres before use preferably have an average diameter of 2 to 20 μm, more preferably 5 to 10 μm. More preferably, hollow microspheres having a median diameter (D50) of 50% cumulative distribution of 6 μm or less are used. The average particle diameter and median diameter can be measured by a laser diffraction particle size distribution analyzer (e.g., Mastersizer 2000, manufactured by Spectris Co., Ltd.). In addition, when using specific commercially available hollow microspheres, the hollow microspheres can be classified to obtain hollow microspheres having a uniform size within a desired range. The classification method is not particularly limited in the present invention, but can be carried out by sieving, centrifugal separation, air classification, dry air classification, or the like.

[0046] The material for the hollow microspheres 4A is added in an amount of preferably 0.1 to 10 parts by mass, more preferably 1 to 7 parts by mass, and even more preferably 1 to 5 parts by mass, based on 100 parts by mass of the urethane prepolymer.

[0047] In addition to the above components, conventionally used blowing agents may be used together with the hollow microspheres 4A within the range that does not impair the effects of the present invention, and a gas that is non-reactive with each of the above components may be blown in during the mixing step described below. Examples of the blowing agent include water and blowing agents mainly composed of hydrocarbons having 5 or 6 carbon atoms. Examples of the hydrocarbon include linear hydrocarbons such as n-pentane and n-hexane, and alicyclic hydrocarbons such as cyclopentane and cyclohexane.

[0048] <Mixing process> In the mixing step, the urethane bond-containing polyisocyanate compound (urethane prepolymer) obtained in the preparation step, additives, curing agent, and hollow microspheres are fed into a mixer and stirred and mixed. The mixing step is carried out in a state where the components are heated to a temperature that ensures the fluidity of each component. However, care must be taken when the components are heated too much, as the hollow microspheres will expand and will no longer have the desired pore distribution.

[0049] <Forming process> In the molding process, the mixture for molding prepared in the mixing process is poured into a rod-shaped mold preheated to 30 to 100°C for primary curing, and then heated at about 100 to 150°C for about 10 minutes to 5 hours for secondary curing to form a cured polyurethane resin (polyurethane resin molded body). At this time, the urethane prepolymer and the curing agent react to form a polyurethane resin, and the mixture hardens. If the viscosity of the urethane prepolymer is too high, the fluidity is poor and it becomes difficult to mix uniformly during mixing. If the temperature is increased to decrease the viscosity, the pot life is shortened, and mixing spots occur, resulting in variation in the size of the hollow microspheres contained in the resulting foam. In particular, if the reaction temperature is too high, when unexpanded hollow microspheres are used, they expand more than necessary, making it difficult to obtain the desired openings. On the other hand, if the viscosity is too low, the bubbles move in the mixture, making it difficult to obtain a foam in which the hollow microspheres are uniformly dispersed. For this reason, it is preferable to set the viscosity of the prepolymer in the range of 500 to 4000 mPa·s at a temperature of 50 to 80°C. This can be achieved, for example, by changing the molecular weight (degree of polymerization) of the prepolymer. The prepolymer is heated to about 50 to 80°C to make it flowable.

[0050] In the molding process, the mixture is reacted in a mold as necessary to form a foam. At this time, the prepolymer is crosslinked and hardened by the reaction between the prepolymer and the hardener.

[0051] After obtaining the molded body, it is sliced ​​into sheets to form a plurality of polishing layers 4. A general slicing machine can be used for slicing. When slicing, the lower layer of the molded body is held, and the molded body is sliced ​​to a predetermined thickness starting from the upper layer. The slice thickness is set to, for example, a range of 1.3 to 2.5 mm. In the case of a foam molded in a 50 mm thick mold, for example, about 10 mm of the upper and lower layers of the foam are not used due to scratches, etc., and 10 to 25 polishing layers 4 are formed from about 30 mm of the center. In the hardening and molding step, a foam is obtained in which hollow microspheres 4A are formed approximately uniformly inside.

[0052] If necessary, grooves may be formed on the polishing surface of the resulting polishing layer 4. In the present invention, the method of forming the grooves and their shape are not particularly limited.

[0053] Thereafter, a double-sided tape is attached to the surface of the polishing layer 4 opposite to the polishing surface of the polishing layer 4 obtained in this manner. There are no particular limitations on the double-sided tape, and any double-sided tape known in the art can be selected and used.

[0054] <Method of manufacturing the cushion layer 6> The cushion layer 6 is preferably made of an impregnated nonwoven fabric impregnated with a resin. Resins for the material of the impregnated nonwoven fabric include polyurethanes such as polyurethane and polyurethane polyurea, acrylics such as polyacrylate and polyacrylonitrile, vinyls such as polyvinyl chloride, polyvinyl acetate and polyvinylidene fluoride, polysulfones such as polysulfone and polyethersulfone, acylated celluloses such as acetylated cellulose and butyrylated cellulose, polyamides and polystyrenes. The density of the nonwoven fabric before being impregnated with the resin (web state) is preferably 0.3 g / cm. 3 More preferably, it is 0.1 to 0.2 g / cm 3 The density of the nonwoven fabric after resin impregnation is preferably 0.7 g / cm. 3 More preferably, it is 0.25 to 0.5 g / cm 3The density of the nonwoven fabric before and after resin impregnation is equal to or less than the upper limit, so that the processing accuracy is improved. Also, the density of the nonwoven fabric before and after resin impregnation is equal to or more than the lower limit, so that the penetration of the polishing slurry into the base layer can be reduced. The adhesion rate of the resin to the nonwoven fabric is expressed as the weight of the attached resin relative to the weight of the nonwoven fabric, and is preferably 50% by weight or more, and more preferably 75 to 200% by weight. The adhesion rate of the resin to the nonwoven fabric is equal to or less than the upper limit, so that the desired cushioning properties can be obtained.

[0055] <Joining process> In the bonding step, the formed polishing layer 4 and cushion layer 6 are bonded (bonded) with an adhesive layer 7. For example, an acrylic adhesive is used for the adhesive layer 7, and the adhesive layer 7 is formed to a thickness of 0.1 mm. That is, the acrylic adhesive is applied to the surface of the polishing layer 4 opposite the polishing surface P with a substantially uniform thickness. The surface of the polishing layer 4 opposite the polishing surface P and the surface of the cushion layer 6 are pressed together via the applied adhesive, and the polishing layer 4 and the cushion layer 6 are bonded with the adhesive layer 7. Then, after cutting into a desired shape such as a circle, an inspection is performed to confirm that there is no dirt or foreign matter attached, and the polishing pad 3 is completed.

[0056] <<Polishing>> The polishing pad having a polishing layer containing the above-mentioned hollow microspheres provides a good polishing rate and has excellent defect performance. The polishing pad of the present invention can be used for various polishing objects such as metals and oxides, without being particularly limited. Preferably, metallic copper, silicon oxide, etc. are mentioned. The settings of the polishing machine during polishing (polishing platen rotation speed, pressure, time, etc.) are not particularly limited, and can be changed as appropriate depending on the condition of the workpiece to be polished and other environmental factors. In addition, a slurry is used during polishing, but in the present invention, one containing abrasive grains may be used. The type of abrasive grains is not particularly limited, and examples thereof include cerium oxide, zirconium oxide, zirconium silicate, cubic boron nitride (CBN), ferric oxide, manganese oxide, chromium oxide, silicon dioxide, alumina, barium carbonate, magnesium oxide, calcium carbonate, barium carbonate, magnesium oxide, and mica. In addition, since the polishing pad of the present invention has specific openings in the cross section (i.e., specific openings in the polishing surface), it is preferable that the abrasive grains have a diameter of 0.01 to 0.2 μm. EXAMPLES

[0057] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0058] In each of the examples and comparative examples, unless otherwise specified, "parts" means "parts by mass".

[0059] In addition, the NCO equivalent is a value indicating the molecular weight of the prepolymer (PP) per NCO group, which is calculated by (mass (parts) of polyisocyanate compound + mass (parts) of polyol compound) / [(number of functional groups per molecule of polyisocyanate compound × mass (parts) of polyisocyanate compound / molecular weight of polyisocyanate compound)-(number of functional groups per molecule of polyol compound × mass (parts) of polyol compound / molecular weight of polyol compound)].

[0060] (Manufacture of abrasive layer A) 100 parts of isocyanate-terminated urethane prepolymer (polyisocyanate compound containing urethane bonds) with an NCO equivalent of 460, which is made by reacting 2,4-tolylene diisocyanate (TDI), poly(oxytetramethylene) glycol (PTMG) and diethylene glycol (DEG), were mixed with 4.5 parts of unexpanded hollow microspheres, the shell of which is made of acrylonitrile-vinylidene chloride copolymer and which contain isobutane gas in the shell, to obtain a mixed liquid. The resulting mixed liquid was charged into a first liquid tank and kept warm. Next, 26.1 parts of MOCA was charged into a second liquid tank as a curing agent separately from the first liquid, and kept warm in the second liquid tank. The liquids in the first liquid tank and the second liquid tank were each injected into a mixer equipped with two injection ports so that the R value, which represents the equivalent ratio of the amino group and hydroxyl group present in the curing agent to the terminal isocyanate group in the prepolymer, was 0.90. The two injected liquids were mixed and stirred while being injected into a mold of a molding machine preheated to 80°C, then the mold was clamped and heated for 30 minutes for primary curing. The primary cured molded product was demolded and then secondary cured in an oven at 120°C for 4 hours to obtain a urethane molded product. The obtained urethane molded product was allowed to cool to 25°C, and then heated again in an oven at 120°C for 5 hours, and then sliced ​​to a thickness of 1.3 mm to obtain an abrasive layer A. For comparison, two types of abrasive layer A were obtained using two types of hollow microspheres.

[0061] (Manufacture of abrasive layer B) Abrasive layer B was obtained by preparing the same method as abrasive layer A, except that the mixed solution of the first liquid used in the preparation of abrasive layer A was 100 parts of an isocyanate group-terminated urethane prepolymer (polyisocyanate compound containing a urethane bond) with an NCO equivalent of 420, and the second liquid used in the preparation of abrasive layer A was 28.8 parts of MOCA. For comparison, two types of hollow microspheres were used, and thus two types of abrasive layer B were obtained.

[0062] (Manufacture of cushion layer) A nonwoven fabric made of polyester fibers was immersed in a urethane resin solution (manufactured by DIC Corporation, product name "C1367"). After immersion, the resin solution was squeezed out using a mangle roller capable of applying pressure between a pair of rollers, and the nonwoven fabric was impregnated with the resin solution approximately uniformly. Next, the nonwoven fabric was immersed in a coagulating liquid made of water at room temperature to coagulate and regenerate the impregnated resin, thereby obtaining a resin-impregnated nonwoven fabric. Thereafter, the resin-impregnated nonwoven fabric was taken out of the coagulating liquid, and further immersed in a cleaning liquid made of water to remove N,N-dimethylformamide (DMF) in the resin, and then dried. After drying, the surface skin layer was removed by buffing treatment to prepare a cushion layer with a thickness of 1.3 mm.

[0063] Examples and Comparative Examples The polishing layers A and B and the cushion layer were bonded with a 0.1 mm thick double-sided tape (a PET substrate with adhesive layers made of acrylic resin on both sides) to produce polishing pads of the examples and comparative examples. The polishing layer A was used in Example 1 and Comparative Example 1, and the polishing layer B was used in Example 2 and Comparative Example 2, and the same cushion layer was used for both cushion layers. The hollow microspheres used were those having the median diameter shown in Table 1 (hollow microspheres before mixing with resin, those classified by dry air classification in Examples 1 and 2, and those not classified in Comparative Examples 1 and 2) to produce polishing pads.

[0064] (density) Density of the polishing layer (g / cm 3 ) was measured in accordance with the Japanese Industrial Standard (JIS K 6505). (D hardness) The D hardness of the polishing layer was measured using a D-type hardness tester in accordance with the Japanese Industrial Standards (JIS-K-6253). Here, the measurement sample was obtained by stacking multiple polishing layers as necessary so that the total thickness was at least 4.5 mm. (Aperture evaluation) The polishing layer obtained by slicing was examined for the pore diameter, pore ratio, and number of pores in the cross section of the polishing layer. The pore diameter, pore ratio, and number of pores were observed by magnifying an area of ​​approximately 0.6 mm square (excluding the groove part) on the surface of the polishing layer by 400 times with a laser microscope (VK-X1000, KEYENCE), and the obtained image was binarized using image processing software (WinROOF2018 Ver4.0.2, Mitani Shoji) to confirm the pores. In addition, the circle equivalent diameter and its average value (average pore diameter) were calculated from the area of ​​each pore. The pore diameter histogram was expressed as one class for each 1 μm range (for example, 20.0 μm or more, less than 21.0 μm, etc.). The cutoff value (lower limit) of the pore diameter was set to 5 μm to exclude noise components. The results are shown in Table 1, Figures 3 and 4. The aperture diameter is the average diameter of the apertures visible in the laser microscope image, the aperture ratio is the ratio of the area of ​​apertures per unit area (0.6 mm square), and the aperture number is the number of apertures per 0.6 mm square. The number and area ratios of apertures 25 μm or larger indicate the number and area ratios of apertures 25 μm or larger out of the total apertures. The same applies to the number and area ratios of apertures 30 μm or larger.

[0065] [Table 1]

[0066] As can be seen from Table 1, the combination of Example 1 and Comparative Example 1, which uses polishing layers made of the same resin, and the combination of Example 2 and Comparative Example 2 have almost the same physical properties such as density and D hardness. However, the average pore size of the polishing layer of Example 1 and Example 2, which uses hollow microspheres with a small median diameter before mixing with the resin, is smaller than that of Comparative Example 1 and Comparative Example 2 (larger than 14 μm in the Comparative Example, whereas Example 1: 12.7 μm, Example 2: 12.0 μm) and the proportion of pores of 25 μm or more is 5% or less (Comparative Example the ratio of holes of 30μ or more was 3% or less (all comparative examples were greater than 3%, while example 1: 1.01% and example 2: 1.00%); and the ratio of holes of 30μ or more was 10% or less (all comparative examples were greater than 10%, while example 1: 6.01% and example 2: 7.70%). As can be seen from the cross-sectional photographs of Figures 3 and 4, Examples 1 and 2 have smaller and more uniformly sized openings than Comparative Examples 1 and 2. Furthermore, the histograms of Figures 3 and 4 show that Examples 1 and 2 have a smaller distribution of large opening sizes (the sum of the number of openings of 25 μm or more is 5% or less of the total number of openings in the cross section of the abrasive layer, the sum of the number of openings in each class of 25 μm or more is 5% or less of the total number of openings in the cross section of the abrasive layer, and the sum of the number of openings in each class of 30 μm or more is 3% or less of the total number of openings in the cross section of the abrasive layer).

[0067] (Polishing performance evaluation) Using the polishing pads of Examples 1 and 2 and Comparative Examples 1 and 2, polishing of a metal film substrate and an oxide film substrate was carried out under the following polishing conditions.

[0068] (polishing conditions) Polishing machine used: F-REX300X (manufactured by Ebara Corporation) Disk: B25 (3M) and A188 (3M) Abrasive temperature: 20℃ Polishing platen rotation speed: 85 rpm Polishing head rotation speed: 86 rpm Grinding pressure: 3.5psi Polishing slurry (metal film): CSL-9044C (CSL-9044C stock solution: pure water = 1:1 weight ratio mixture) (manufactured by Fujimi Corporation) Polishing slurry (oxide film): PL6115 (PL6115 stock solution: pure water = 1:1 weight ratio mixture) Polishing slurry flow rate: 200ml / min Polishing time: 60 seconds Object to be polished (metal film): Cu film substrate Polished object (oxide film): Silicon wafer with TEOS (Tetra Ethyl Ortho Silicate) Pad break: 35N 10 minutes Conditioning: Ex-situ, 35N, 4 scans

[0069] (polishing rate) The polishing pad was placed in a predetermined position on the polishing device using double-sided tape with an acrylic adhesive, and polishing was performed under the above-mentioned polishing conditions. The polishing rates (unit: angstroms) of the 15th, 25th, and 26th substrates polished for the metal film substrates and the polishing rates (unit: angstroms) of the 10th, 15th, 25th, 50th, 60th, 75th, 90th, and 100th substrates polished for the oxide film substrates were measured. The polishing results for the metal film substrates are shown in Figure 5(a), and the polishing results for the oxide film substrates are shown in Figure 6(a).

[0070] (Defect) For the metal film substrates, the 27th, 28th, and 50th substrates polished, and for the oxide film substrates, the 10th, 25th, 37th, 50th, 60th, 75th, 90th, and 100th substrates polished, defects with a size of 90 nm or more were detected using the high sensitivity measurement mode of a surface inspection device (KLA-Tencor, Surfscan SP2XP). For each detected defect, the SEM image taken with a review SEM was analyzed, and the number of each type, "Particles", "Pad Debris", and "Scratch", was counted. The polishing results of the metal film substrate and the oxide film substrate are shown in Figure 5(b) and Figure 6(b), respectively. The fewer the number of defects (particles, pad debris, and scratches), the fewer the defects and the better the result. In the polishing results for the metal film substrate, no difference was observed in terms of particles and pad debris between the examples and comparative examples, so the number of scratches is shown. In addition, in the polishing results for the oxide film substrate, only the results for Example 1 and Comparative Example 1 are shown, but the same tendency was observed in Example 2 and Comparative Example 2.

[0071] As can be seen from the polishing results shown in Figures 5 and 6, in both metal film polishing and oxide film polishing, the polishing pads of Examples 1 and 2 have the same polishing rate as the polishing pads of Comparative Examples 1 and 2, which have similar physical properties, while the number of defects is smaller than that of the comparative examples. In particular, it can be seen that there is a significant reduction in "scratches" in metal film polishing and oxide film polishing, and "particles" and "pad debris" on the oxide film substrate compared to the comparative examples. [Industrial Applicability]

[0072] The present invention contributes to the manufacture and sale of polishing pads and has industrial applicability.

[0073] 1 Polishing equipment 3 Polishing Pads 4 Polishing layer 4A Hollow microsphere 6 Cushioning Layer 7 Adhesive layer 8 Object to be polished 9. Slurry 10 Polishing plate

Claims

1. A polishing pad having a polishing layer having a polishing surface for polishing an object to be polished, the polishing layer includes hollow microspheres that form hollow bodies within the polishing layer; The cross section of the polishing layer has an average pore size of 10 to 14 μm, In a histogram of opening diameters of a cross section of the polishing layer, the range of 1 μm is expressed as one class, the sum of the number of pores having a size of 25 μm or more is 5% or less of the total number of pores in the cross section; A polishing pad, wherein the sum of the open area of ​​each class of 25 μm or more is 20% or less of the total open area of ​​said cross section.

2. 2. The polishing pad of claim 1, wherein the sum of the number of openings in each class of 30 μm or more is 3% or less of the total number of openings in the polishing surface, and the sum of the opening area in each class of 30 μm or more is 10% or less of the total opening area in the polishing surface.

3. 3. The polishing pad of claim 1, wherein the hollow microspheres are derived from unexpanded hollow microspheres having a median diameter (D50) of 6 μm or less.

4. A method for manufacturing a polishing pad having a polishing layer having a polishing surface for polishing an object to be polished, comprising the steps of: the polishing layer includes hollow microspheres that form hollow bodies within the polishing layer; The cross section of the polishing layer has an average pore size of 10 to 14 μm, In a histogram of opening diameters of a cross section of the polishing layer, the range of 1 μm is expressed as one class, the sum of the number of pores having a size of 25 μm or more is 5% or less of the total number of pores in the cross section; The sum of the open area of ​​each class of 25 μm or more is 20% or less of the total open area of ​​the cross section, The polishing layer is formed by mixing and reacting a urethane bond-containing polyisocyanate compound, a curing agent, and unexpanded hollow microspheres having a median diameter (D50) of 6 μm or less.

5. The process of claim 4, wherein the reaction is carried out under temperature control so as not to exceed 140°C.

6. A polishing method for polishing an object to be polished using a polishing pad and abrasive grains, comprising the steps of: The polishing pad includes a polishing layer having a polishing surface for polishing an object to be polished, the polishing layer includes hollow microspheres that form hollow bodies within the polishing layer; The cross section of the polishing layer has an average pore size of 10 to 14 μm, In a histogram of opening diameters of a cross section of the polishing layer, the range of 1 μm is expressed as one class, the sum of the number of pores having a size of 25 μm or more is 5% or less of the total number of pores in the cross section; The sum of the open area of ​​each class of 25 μm or more is 20% or less of the total open area of ​​the cross section, The abrasive grains have a diameter of 0.01 to 0.2 μm; A polishing method comprising the steps of: bringing the object to be polished into contact with the polishing surface of the polishing pad in the presence of the abrasive grains; and rotating either or both of the polishing pad and the object to be polished, thereby performing polishing.

Citation Information

Patent Citations

  • permeable microporous material for cmp

    JP2008546550A

  • Polishing pad

    JP2017177301A

  • Porous polyurethane polishing pad and method for production thereof

    JP2019195901A

  • Polishing pad

    JP2020049621A

  • Polishing pad and method for manufacturing the polishing pad

    JP2019069497A